NO SQL (NOT ONLY SQL) DataBases: A Review - Kumar, Kiran BG; Unki, Prakash H (International Journal of Computer Sciences and Engineering, 2025)
This Review portrays the significance of NoSQL databases in the field of Big Data and distributed computing. Because a number of clients added to cloud computing and since they produce the huge volume of organized, unstructured and semi-structured information, to deal with these kinds of information NoSQL databases are preferred. This survey helps to analysis the data models of NoSql and its advantages and limitations of NoSql and relational databases. In the end, the Review concludes with various reasons to adopt NoSQL in Big Data and Cloud computing